UI Generosity and Job Acceptance: Effects of the 2020 CARES Act - Nicolas Petrosky-Nadeau; Robert G. Valletta (Institute of Labor Economics (IZA), 2021)
To provide economic relief following the onset of the COVID-19 pandemic, the U.S. CARES Act granted an extra 600 per week in unemployment insurance (UI) benefit payments from late March through July 2020. This unprecedented increase in UI generosity caused weekly benefit payments to exceed prior earnings for most recipients, raising concern that many would be unwilling to accept job offers, slowing the labor market recovery. To assess the impact of the UI supplement, we analyze the job acceptance decision in a dynamic framework in which job seekers weigh the value of a job against remaining unemployed, accounting for the perceived state of the labor market and expected weeks of UI benefits. We derive a reservation level of benefit payments at which an individual is indifferent between accepting and refusing a job offer at their prior wage. Calculating the reservation benefit and comparing it to imputed benefit payments for a wide range of U.S. workers suggests that only a small fraction would turn down an offer to return to work at their previous wage under the CARES Act expanded UI payments. We supplement this quantitative assessment of reservation benefits with direct empirical analysis of labor force transitions using matched Current Population Survey (CPS) data, linked to annual earning records from the CPS income supplement to form UI replacement rates. The results show moderate disincentive effects of the 600 supplemental payments on job finding rates and by extension small effects of the 300 weekly supplement available during 2021.
Keywords: J64; J65; 330; unemployment; unemployment insurance; job acceptance; COVID-19; CARES Act